Feral children: settler colonialism, progress, and the figure of the child. (2nd January 2018) - Rollo, Toby
ABSTRACT: Settler colonialism is structured in part according to the principle of civilizational progress yet the roots of this doctrine are not well understood. Disparate ideas of progress and practices related to colonial dispossession and domination can be traced back to the Enlightenment, and as far back as ancient Greece, but there remain unexplored logics and continuities. I argue that civilizational progress and settler colonialism are structured according to the opposition between politics governed by reason or faith and the figure of the child as sinful or bestial. Thus, it is not contingent, but rather necessary that justificatory frameworks of European empire and colonialism depict Indigenous peoples as children. To illustrate how the theoretical link between Indigenous peoples and children emerges not as a simple analogy, but rather, as the source of the premodern/modern and savage/civilized binaries, I trace the various historical iterations of the political/childhood opposition through the classical, medieval, enlightenment, and modern eras. I show how the model of civilizational progress from a premodern and savage state of childhood continues to serve as the model for settler colonial exclusion and domination of Indigenous peoples.